Impact Of Covid-19 Driven Performance Changes on Entities’ Voluntary Disclosures in Statutory Financial Statements – The Evidence from Warsaw Stock Exchange - Wojciech HASIK (Communications of International Proceedings, 2021)
The purpose of the paper is to examine the way Covid-19 influenced the disclosures made by financial statement preparers in the statutory financial statements. The pandemic was strong but one-off factor that stressed performance of many companies. That makes it difficult to stakeholders to distinguish between business model specific changes to entity’s performance and external,  non-recurring factors that are materially disrupting the prospective dimension of financial information. Qualitative feature of usefulness requires companies to deliver fully comparable financial information to stakeholders. Thus one of the important question is: how preparers of financial statements cope with providing fully comparative information in the financial statement prepared for Covid-19 dominated year. The focus in the paper was made on the actual practices of companies quoted on Warsaw Stock Exchange – the biggest regulated market of EME region with the stress on entities whose performance was heavily deteriorated by pandemic. The research method took detailed and thorough analysis of consolidated financial statements for the year 2020 prepared by companies chosen to the research sample. Even though the sample was limited, the results bring clear evidence that observed regularity was evident: managers of strongly affected companies have strong incentive to extend significantly the range of additional, voluntary disclosures explaining the negative impact of one-off event being out of managers’ control. Even though additional disclosures are hardly supportive to comparativeness of financial information.
Keywords: Quality of Financial Information; Obligatory Disclosure; Voluntary Disclosure; Financial Reporting Practice